2020
DOI: 10.13057/biodiv/d211133
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of bacteria isolated from culture medium of the gold-lipped pearl oyster Pinctada maxima larvae

Abstract: Abstract. Wullur S, Napitupulu H, Wantania LL, Ginting EL, Mamangkey NGF, Smolak R, Ogello E. 2020. Molecular identification of bacteria isolated from culture medium of the gold-lipped pearl oyster Pinctada maxima larvae. Biodiversitas 21: 5291-5297.  This study was conducted for the molecular identification of bacteria species isolated from culture medium of the gold-lipped pearl oyster, Pinctada maxima larvae. The pearl oysters were cultured using live-microalgae (Isochrysis sp) and fish waste diet (FWD) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In recent years, related research on P . maxima have focused on larval breeding (Ompi et al, 2018; Wang et al, 2017; Wullur et al, 2020), growth performance (Hao et al, 2019; Wang et al, 2019), pearl cultivation (McDougall et al, 2016, 2021; Wei et al, 2017), shell materials (Alakpa et al, 2018; Anggraini et al, 2019), disease (Goncalves et al, 2017) and genetic diversity (Lind et al, 2009; Nayfa & Zenger, 2016). Previous studies on the effects of salinity on P .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, related research on P . maxima have focused on larval breeding (Ompi et al, 2018; Wang et al, 2017; Wullur et al, 2020), growth performance (Hao et al, 2019; Wang et al, 2019), pearl cultivation (McDougall et al, 2016, 2021; Wei et al, 2017), shell materials (Alakpa et al, 2018; Anggraini et al, 2019), disease (Goncalves et al, 2017) and genetic diversity (Lind et al, 2009; Nayfa & Zenger, 2016). Previous studies on the effects of salinity on P .…”
Section: Introductionmentioning
confidence: 99%
“…The pearl oyster is mainly distributed in the central Indo-Pacific region, including the Australia, Indonesia, Japan, Micronesia, Papua New Guinea, Philippines, Polynesia and South China Sea (Liang et al, 2016). In recent years, related research on P. maxima have focused on larval breeding (Ompi et al, 2018;Wang et al, 2017;Wullur et al, 2020), growth performance (Hao et al, 2019;Wang et al, 2019), pearl cultivation (McDougall et al, 2016Wei et al, 2017), shell materials (Alakpa et al, 2018;Anggraini et al, 2019), disease (Goncalves et al, 2017) and genetic diversity (Lind et al, 2009;Nayfa & Zenger, 2016). Previous studies on the effects of salinity on P. maxima focus on growth and survival rate (Deng et al, 2013;Taylor et al, 2004), and there is still a blank about the influence of salinity stress on the immune and antioxidant indexes of P. maxima.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with salinity 30 ppt, Taylor et al (2004) pointed out that the growth of P. maxima was significantly depressed at a salinity of 25 ppt, 40 ppt, and ppt, and the results of Deng et al (2013) showed that the growth and survival rate of P. maxima larvae declined at the salinity of ppt, 24 ppt, and 21 ppt. Furthermore, in recent years, the research about genetic diversity, pearl cultivation, larval reproduction, growth performance, shell materials, and disease have been documented in P. maxima (Lind et al, 2009;Nayfa and Zenger, 2016;Ompi et al, 2018;Anggraini et al, 2019;Hao et al, 2019;Wang et al, 2019a;Wullur et al, 2020;McDougall et al, 2021). Therefore, more information is needed on the effects of salinity stress on the P. maxima, as P. maxima is often cultured in offshore areas that are subject to fluctuating salinity.…”
Section: Introductionmentioning
confidence: 99%